Entrepreneurial potential of rural territories as an object of scientific research - Iryna Kravchuk; Alexander Rakovich (Agricultural and Resource Economics, 2018)
Purpose. The purpose of the research is to substantiate the prospects of theoretical, methodological and applied provision of entrepreneurial potential of rural areas taking into account the current trends in the development of socio-economic-territorial systems. Methodology / approach. The methodological basis of the research is the abstract-logical method, methods of analysis and synthesis, by means of which theoretical generalizations of the concepts of the entrepreneurial potential of territories, classification of periods of their development and transformations were made. Results. The need to study the problems of entrepreneurial potential of rural areas is due to the lack of experience and knowledge of the leaders of various organizations, heads of private peasant farms in relation to its formation and reproduction, the implementation of business communications, inadequate methodological and applied to ensure its adaptation to the existing conditions of territorial development. The article analyzes the content of the economic category «entrepreneurial potential of rural territories», identifies the preconditions for forming the theoretical basis of entrepreneurial potential of rural territories, identifies the stages of its evolution and outlines the prospects for its theoretical, methodological and applied support. Originality / scientific novelty. The originality of the research is determined by the classification of the evolution of the concept of entrepreneurial potential of rural territories with the allocation of six stages, in which there is a manifestation of causal relationships of economic development of territories with entrepreneurial activity, oriented on the economic growth of socio-economic-territorial systems. Practical value / implications. The significance of the research is due to the prospects of the theoretical, methodological and applied provision of entrepreneurial potential of rural areas in particular, considering its integration (aggregate) features, the resource component, the environment for its reproduction, the effective use of institutional, managerial, and endogenous potentials.